NILAI PERJUANGAN PEMUDA DALAM NOVEL NGRANGGEH LINTANG PANDJER SORE KARYA SRI HADIDJOJO - Mutiara Yusi Nanda Seti; Dwi Aprilia Nur Alifah; Sawitri (CV. Kalimasada Group, 2025)
This study aims to examine the effectiveness of using Islamic story media in improving students' writing skills at a certain educational level. The background of this research is based on the need to develop contextual learning media embedded with religious values to stimulate motivation and writing learning outcomes. The study employed a quantitative approach with an experimental design comparing an experimental group using Islamic story media and a control group using conventional methods. Data were collected through pretest and posttest writing skills assessments, and analyzed using descriptive and inferential statistics. The results showed that the experimental group experienced a significant improvement in writing skills scores compared to the control group, with statistically higher posttest mean scores. In conclusion, the use of Islamic story media is effective as a learning medium to enhance students' writing skills and contributes to character development through the integration of religious values. Practical implications and recommendations for further research are also presented.